Pentingnya Pemahaman Mandi Wajib Dan Sholat Bagi Siswa Kelas V Dan VI SDN 6 TAMBUN - Nimah Wahyuni; Muliyani; Sri Wulandari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This community service activity includes material on the correct procedures for praying and obligatory bathing. This activity is important to carry out because it is very beneficial fer the community, including students of SDN 6 Tambun class V and VI. The aim of this community service process is for class V and VI students to know more about obligatory bathing and the correct prayer sistem. As obligatory bathing is a physical cleasing prosess which is the obligation of a muslims, it is aimen at cleansing and perifying the body from the main hadas. Meanwhile, prayer is a from of woeship that must be carred out by every muslim at a specified time. The method use is grup cooperation with theoretical explanation teachniquen, demonstration by students and individual practice. The results obtained are that students understand more about obligatory bathing and are no lenger mistaken about the procedures for obligatory prayers.